رواة الصحيحين الذين تكلم فيهم ابن حبان فى كتابه المجروحين: دراسة نقدية تطبيقية - العواجي، عبدالرحمن بن أحمد (جامعة الإمام محمد بن سعود الإسلامية, 2016)
خلص البحث إلى أن من رواة الصحيحين من هو متكلم فيه. وأن البخاري ومسلما اتبعا منهج الانتقاء من أحاديث المتكلم فيهم للتخريج لهم في الصحيح. وبعد دراسة أحوال الرواة الذين تكلم فيهم ابن حبان. تبين التالي: أ‌- الرواة الذين تكلم في فيهم بكثرة الخطأ والوهم، ترجح أنهم ما بين ثقة، وصدوق، ولا بأس به. وصدوق يخطئ. ب‌- الرواة الذين تكلم فيهم بالاختلاط. تبين أنهم لم يخرج لهم الشيخان عمن سمع منهم بعد الاختلاط، وليس لهم في الصحيحين ما ينكر عليهم. ت‌- توقف ابن حبان في راو من هؤلاء السبعة، وهو عمران بن مسلم المنقري. ووصفه بأنه ممن يستخير الله فيه، وبعد دراسة حاله تبين أنه لا بأس به. أن من حكم بمجرد رواية الشيخين عن الراوي بأنه من شرط الصحيح فقد غفل وأخطأ. بل ذلك يتوقف على النظر في كيفية الرواية عنه. وعلى أي وجه، وأن تخريج صاحب الصحيح لراو مقتض لعدالته عنده، وصحة ضبطه. وهذا مقيد بمن أخرج لهم في الأصول، لا ما أخرج في المتابعات أو الشواهد.
This is a study of some of the Hadeeth narrators who were negatively reported by Ibn Hibban, and the method Al-Bukhari and Muslim usedin selecting the Hadeeths of those questioned narrators to authenticate their narrations in the SaHeeH. After studying the status of those narratorsin Ibn Hibban's book, the researcher concludes the following: (a) The narrators whose narrations are judged to be full of (mistake and illusion), are more likely tobe classified asreliable, truthful, acceptable, and mistaken truthful. (b) For the narrators whose narrations are accused of confusion according to Ibn Hibban, the two Imams did not authenticatethe narrations after this confusion, nor were the denied narrations mentioned in the SaHeeHayn. (c) Ibn Hibban hesitated in judgingone of the seven narrators, Omran Ibn Muslim Al-Munqari, and said that he sought intuitive inspiration from Allah to guide him to the right verdict.But after studying Al-Munqari'sstatus, it appears that he is acceptable. Moreover, those who judge narrators only by the narration of Al-Bukhari and Muslim as being sound are mistaken. It depends on the consideration of the narration after the narrator and its condition,and on the authenticating of a narration by one of the Imamsas being just and soundly verified beside the narrator's righteousness; however, this was limited to those whose narrations were included by Ibn Hibban in the fundamentals not in Al-Mutaaba'aat (the follow up) or citations.
Keywords: علم الحديث -- علم الجرح والتعديل -- تراجم الرواة -- أبو حاتم البستي، محمد بن حبان بن أحمد، ت. 354 هـ. -- المجروحين -- الصحيحين